The Synergistic Effects of Celastrol in combination with Tamoxifen on Apoptosis and Autophagy in MCF-7 Cells - Lijun Wang; Luqun Tang; Chengyun Yao; Chunyan Liu; Yongqian Shu (Journal of Immunology Research)
Breast cancer is one of the most common cancers among females and is associated with high mortality and morbidity rates. Several studies have demonstrated that combination treatments with natural products and tamoxifen can improve the sensitivity and cytotoxicity of oestrogen-positive breast cancer cells in response to tamoxifen. Celastrol, a triterpene from traditional Chinese medicine, has been proven to exert significant anticancer effects on various cancers. Our study is aimed at exploring the interactive antitumour effects of celastrol combined with tamoxifen and the potential underlying anticancer mechanisms in MCF-7 cells. The results from MTT assays, isobolographic analyses, and clonogenic cell survival assays revealed that a combination of celastrol and tamoxifen exerted synergistic cytotoxic effects in MCF-7 cells. The results from Annexin V/PI staining and flow cytometry analysis suggested that celastrol enhanced tamoxifen-mediated apoptosis. In addition, exposure to a combination of celastrol and tamoxifen inhibited cell proliferation by causing G1 phase cell cycle arrest. Moreover, the distribution of LC3 was monitored by immunofluorescence, and the changes in the LC3II and P62 levels detected by western blot analysis suggested that celastrol in combination with tamoxifen triggered autophagy. Furthermore, the decrease in p-Akt and p-mTOR in MCF-7 cells, along with the increase in the autophagy marker proteins LC3II and P62, suggested that the Akt/mTOR pathway might be involved in the triggering of cell autophagy by the combination treatment. However, in an MCF-7-implanted nude mouse model, it was possible to detect significantly decreased tumour volumes and tumour weights and decreased p-Akt and p-mTOR protein expression in the celastrol+tamoxifen group. Therefore, our study provides the first evidence that celastrol combined with tamoxifen exerts synergistic anticancer effects by inducing apoptosis and autophagy in MCF-7 cells. Considering the urgent need for novel therapeutic strategies in anticancer therapy, this combinatorial approach is worthy of further investigation.